2-deoxy-D-glucose enhances dichloroacetate antitumor action against lewis lung carcinoma - Pyaskovskaya, O.N.; Kolesnik, D.L.; Fedorchuk, A.G.; Prochorova, I.V.; Solyanik, G.I. (Experimental Oncology, 2016)
Aerobic glycolysis that supports high proliferation rate and survival of tumor cells in unfavorable conditions is among fundamental features of tumor metabolism. The search for active modulators of energetic metabolism capable of suppressing tumor growth and metastasis could result in higher effectiveness of anticancer therapy. Aim: To study antitumor and antimetastatic activity of the modulators of energetic metabolism dichloroacetate (DCA) and 2-deoxy-D-glucose (2DG) used in combination treatment of Lewis lung carcinoma (LLC). Materials and Methods: As experimental tumor model, LLC/R9 variant was used. DCA and 2DG were administered per os to С57Bl/6 mice 5 times per week for 3 weeks at a total dose of 1.5 and 0.98 g/kg, respectively, as single agents or in combination starting from the following day after tumor cell transplantation. Growth of primary tumor and number and volume of lung metastases were registered. Lactate and pyruvate content was determined by enzymatic methods using lactate dehydrogenase. Electron paramagnetic resonance was used for analyzing the functional state of the components of mitochondrial respiratory chain. Engulfing activity and reactive oxygen species (ROS) production in tumor-associated СD14⁺cells was analyzed by flow cytometer with the use of FITC-labeled staphylococcus, and by spectrofluorometry with the use of 2.7-dichlorofluorescein diacetate, respectively. Results: DCA administered as a single agent did not affect primary tumor growth but decreased the number and volume of lung metastases by 60% (p < 0.05) and 90% (p < 0.05), respectively. In mice treated with 2DG only, primary tumor volume as well as the number and volume of lung metastases were not affected. Combination treatment with DCA and 2DG resulted in the decrease of primary tumor volume, the number and volumes of lung metastases by 70; 46, and 90%, respectively (р < 0.05). High antitumor activity of DCA + 2DG was associated with 31% decrease (p < 0.05) of lactate content in tumor tissue and 120% increase (p < 0.01) of ROS production in СD14⁺ cells recruited to the region of tumor growth. Conclusion: 2DG that possesses neither antitumor nor antimetastatic activity against LLC/R9 significantly enhanced antitumor activity of DCA with accompanying inhibition of glycolysis and increase of cytotoxic activity of СD14⁺cells infiltrating tumor tissue. Taking into account significant antimetastatic activity of DCA this substance could be considered as a promising antimetastatic agent.